Popular History: Historical Awareness of Digital Gaming in Finland from the 1980s to the 2010s - Suominen Jaakko (Finland, 2022)
This paper studies the popular historiography of digital gaming. By using the Finnish context as a case example and analyzing hundreds of popular game-history-related articles, mostly from computer and game hobbyist magazines and newspapers, the paper presents a categorization of four different waves of historical awareness. All the waves emphasized different ways of writing and presenting game history, some focusing more on global issues and some on national and local phenomena. Some of the material was more oriented to personal or individual experiences and some merely toward the collective or general characteristics of gaming. The four-wave categorization and presented topics can be applied to other game historiographical studies to create a richer picture of how the academic and popular histories of games and game cultures have been written.
DiGRA ’20 : Proceedings of the 2020 DiGRA International Conference: Play Everywhere